Stridor in Asian Infants: Assessment and Treatment. (19th February 2012) - Yee-Hang, Wong Birgitta; Theresa, Hui; So-lun, Lee; Wai-Kuen, Ho; Ignace, Wei William
Abstract : Stridor is the main symptom of upper airway obstruction in infants. It can be congenital or acquired, acute or chronic. Pathologies can be located from the nose down to the trachea. Common causes include laryngomalacia, vocal cord palsy, subglottic stenosis, tracheal anomaly, laryngeal cleft, vascular and lymphatic malformation, laryngeal papillomas, craniofacial abnormalities and even head and neck tumours. In this paper, we will discuss our approach to infants with stridor including assessment with flexible and rigid endoscopy and treatments to various conditions in a tertiary centre. Causes of stridor in infants undergoing rigid laryngotracheobronchoscopy in Queen Mary Hospital, University of Hong Kong Medical Centre between 2005 and 2011 will be retrospectively reviewed. Treatments according to various conditions will be discussed. Successful management of these neonates requires accurate diagnosis, early intervention, and multidisciplinary care by ENT surgeons, paediatricians, and paediatric anaesthetists.